2009
DOI: 10.3233/jad-2009-1087
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Reverses Cognitive Impairment and Decreases Brain Amyloid-β Levels in Aged Alzheimer's Disease Mice

Abstract: We have recently shown that Alzheimer's disease (AD) transgenic mice given a moderate level of caffeine intake (the human equivalent of 5 cups of coffee per day) are protected from development of otherwise certain cognitive impairment and have decreased hippocampal amyloid-beta (Abeta) levels due to suppression of both beta-secretase (BACE1) and presenilin 1 (PS1)/gamma-secretase expression. To determine if caffeine intake can have beneficial effects in "aged" APPsw mice already demonstrating cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
230
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(249 citation statements)
references
References 64 publications
11
230
3
5
Order By: Relevance
“…When measuring cognitive performance, caffeine equivalent to that in seven or ten cups of coffee impaired reference memory (which contributed to the improvement seen in working memory), but no impairment was seen at the highest dose of coffee (0.825 %, equivalent to 15 cups a day). These results are in contrast to those of other studies that found that caffeine improves measures of learning and memory in AD transgenic mice (Arendash et al 2006;Arendash et al 2009). However, when normal wildtype mice were treated long-term with caffeine from adulthood through old age, no cognitive benefit was found ).…”
Section: Discussioncontrasting
confidence: 99%
“…When measuring cognitive performance, caffeine equivalent to that in seven or ten cups of coffee impaired reference memory (which contributed to the improvement seen in working memory), but no impairment was seen at the highest dose of coffee (0.825 %, equivalent to 15 cups a day). These results are in contrast to those of other studies that found that caffeine improves measures of learning and memory in AD transgenic mice (Arendash et al 2006;Arendash et al 2009). However, when normal wildtype mice were treated long-term with caffeine from adulthood through old age, no cognitive benefit was found ).…”
Section: Discussioncontrasting
confidence: 99%
“…In this context, caffeine administration has been reported to reverse cognitive impairment and amyloid b (Ab) levels in transgenic Alzheimer's disease model mice (Arendash et al 2009). To examine the protective effects of coffee in a genetically tractable model, we investigated the effects of aqueous coffee extracts in a C. elegans model of Ab toxicity (Link et al 2003).…”
mentioning
confidence: 99%
“…Substantial evidence from human epidemiological studies and from experimental studies conducted in animals and cultured cell models indicate that caffeine, when ingested chronically, can decrease Aβ levels, protect against the onset and severity of AD, and in some cases it can reverse behavioral and pathological features of AD [19,21,24,29]. Less clear, however, are the mechanisms by which caffeine exhibits these protective features.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that it can reverse behavioral and pathological features of AD [19,21,22,24,25,[29][30][31][32][33]. Importantly, these protective effects of caffeine are observed using pharmacologically relevant doses [28,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation